2022
DOI: 10.3390/ijerph19084723
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Association between Sarcopenia and Cognitive Impairment among Older Adults in Rural Malaysia

Abstract: Sarcopenia is a condition that is highly prevalent among older adults. This condition is linked to numerous adverse health outcomes, including cognitive impairment that impairs healthy ageing. While sarcopenia and cognitive impairment may share a common pathway, limited longitudinal studies exist to show the relationship between these two conditions. Therefore, this study aimed to examine the longitudinal association between sarcopenia and cognitive impairment. This is a cohort study among older adults residin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 53 publications
2
18
0
Order By: Relevance
“…The relationship between sociodemographic variables and mental health shows that women have a higher incidence of anxiety, and people with fewer years of education have a higher incidence of depression and anxiety. This is concordant with studies conducted in Madrid (2020) on the health of the elderly during the pandemic; there was a high degree of mortality in older adults of advanced age, and economic situation was associated with diseases and loneliness [ 7 , 25 , 37 , 38 ].…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The relationship between sociodemographic variables and mental health shows that women have a higher incidence of anxiety, and people with fewer years of education have a higher incidence of depression and anxiety. This is concordant with studies conducted in Madrid (2020) on the health of the elderly during the pandemic; there was a high degree of mortality in older adults of advanced age, and economic situation was associated with diseases and loneliness [ 7 , 25 , 37 , 38 ].…”
Section: Discussionsupporting
confidence: 89%
“…Therefore, by Supreme Decree No. 044-2020-PCM published on Sunday, 15 March 2020, in the official gazette El Peruano, the government declared a state of national emergency due to the serious circumstances affecting the life of the nation as a result of the COVID-19 outbreak [ 7 ]. The government adopted measures of mandatory social isolation (quarantine), restricting the exercise of constitutional rights related to personal freedom and security, inviolability of the home, freedom of assembly and transit in the territory, and access to essential services and goods, with restrictions on commercial activity, cultural activities, establishments, recreational activities, and hotels and restaurants, as well as the temporary closure of borders and reduction in transportation supply.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several previous studies have demonstrated the association between sarcopenia and cognitive impairment among general population. 12,[18][19][20] They showed that participants with possible sarcopenia or sarcopenia at baseline were more likely to develop new-onset cognitive impairment in longitudinal analyses. Actually, sarcopenia status may constantly change; therefore, these prognostic values for cognitive impairment might also change over time, especially for HD patients.…”
Section: Introductionmentioning
confidence: 99%